On Contemporary Problems of Communication between Secular and Religious Actors and Ways of its Solution - F. S. Frantsev (Vestnik MGIMO-Universiteta)
The article enlightens questions of communication between secular and religious actors during their political and civil activities. The author draws the reader's attention towards problems that occur in light of high-level secularisation of modern society and suggests their possible solution based on a work by one of the most outstanding west-european philosophers of our time